La compraventa sobre el bien ajeno en el Perú y sus fuentes: ¿validez o ineficacia? - Villota Cerna, Marco Antonio (2022)
This article deals with the trading of other’s property in Peru as to whether it constitutes a case of invalidity or ineffectiveness of the contract, based on the different jurisprudence and doctrine that has been produced on the matter. This is based on a historical and comparative study of the contract of sale in Roman Law and in the various civil law legislations, including the figure of the sale of another’s property and the treatment of the registry rules. In the case of Peru, the influence of comparative law in the regulation of the sales contract is analyzed and how it has influenced the different interpretation of the sale of another’s property and the registry rules. Additionally, an analysis is made of the different cases of sale and purchase of another’s property, the corresponding remedies, the concordance with the registry rules; and finally, the corresponding conclusions are drawn.